EVALUATION OF THE ESSENTIAL OIL OF FOENICULUM VULGARE MILL (FENNEL) FRUITS EXTRACTED BY THREE DIFFERENT EXTRACTION METHODS BY GC/MS - Hammouda, Faiza Mohamed; Saleh, Mahmoud Abbas; Abdel-Azim, Nahla Sayed; Shams, Khaled Ahmed; Ismail, Shams Imbaby; Shahat, Abdelaaty Abdel-Aziz; Saleh, Ibrahim Ahmed (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Hydrodistillation (HD) and steam-distillation, or solvent extraction methods of essential oils have some disadvantages like thermal decomposition of extracts, its contamination with solvent or solvent residues and the pollution of residual vegetal material with solvent which can be also an environmental problem. Thus, new green techniques, such as supercritical fluid extraction and microwave assisted techniques, are potential solutions to overcome these disadvantages. Materials and Methods: The aim of this study was to evaluate the essential oil of Foeniculum vulgare subsp. Piperitum fruits extracted by three different extraction methods viz. Supercritical fluid extraction (SFE) using CO2, microwave-assisted extraction (MAE) and hydro-distillation (HD) using gas chromatography-mass spectrometry (GC/MS). Results: The results revealed that both MAE and SFE enhanced the extraction efficiency of the interested components. MAE gave the highest yield of oil as well as higher percentage of Fenchone (28%), whereas SFE gave the highest percentage of anethol (72%). Conclusion: Microwave-assisted extraction (MAE) and supercritical fluid extraction (SFE) not only enhanced the essential oil extraction but also saved time, reduced the solvents use and produced, ecologically, green technologies.